Musical Mnemonics Enhance Verbal Memory in Typically Developing Children - Knott, David; Thaut, Michael H. (Frontiers in Education, 2018)
The purpose of this study was to compare the effects of musical mnemonics versus spoken word in training verbal memory in children. A randomized control trial of typically-developing 9-11 year old children was conducted using the Rey Auditory Verbal Learning Test (RAVLT), a test measuring a participant’s ability to recall a list of 15 words over multiple exposures. Members of the group who listened to words sung to them recalled an average of 20% more words after listening to and recalling an interference list than members of the control group who listened to the same words spoken. This difference persisted, though slightly smaller (17%) when participants recalled words after a 15-minute waiting period. Additionally, group participants who listened to words sung demonstrated a higher incidence of words recalled in correct serial order. Key findings were all statistically significant at the P<0.05level. Enhanced serial order recall points to the musical pitch/rhythm structure enhancing sequence memory as a potential mnemonic mechanism. No significant differences were found in serial position effects between groups. The findings suggest that musical mnemonic training may be more effective than rehearsal with spoken words in verbal memory learning tasks in 9-11 year olds.